Exploring the effectiveness of virtual reality-based training for sustainable health and occupational safety in industry 4.0 - Yousef Qawqzeh; Ata Al Shraah; Ali Rizwan; Manuel Sánchez-Chero; Leandro Alonso Vallejos More; Mohammad Shabaz (Scientific Reports)
Abstract Nowadays, the use of virtual reality (VR) for training purposes has increased manifold among organizations due to better integration of both cognitive and emotional dimensions. VR-based training surpasses traditional methods in Industry 4.0 by increasing safety awareness by 30%, enhancing risk perception, and improving self-efficacy. A quasi-experimental study involving 200 participants confirmed the superiority of VR through statistical analysis, highlighting its role in fostering a proactive safety culture and promoting sustainable workplace health. The research primarily focuses on how VR-based training can enhance the sustainability of occupational safety for industrial workers, thereby reducing the likelihood of human errors and industrial accidents. A quasi-experimental design was employed in the current study, with 200 participants divided into two groups: intervention and control. The effectiveness of VR-based training was judged based on participants’ self-efficacy toward leadership support, training resources, and communication channels. Findings revealed statistically significant differences between the groups, as shown by the Mann-Whitney U test. Compared to the control group, the intervention group performed significantly better on several indicators, such as the efficacy of the VR training (mean rank = 30.00) and how participants perceived their ability after completing the OSH training based on VR (mean rank = 74.0); further, the findings from the current study revealed that participants who had VR training resources available felt that these were more accessible and better quality than those in the control group (median = 65) than intervention group (median = 72) significant at (p = 000). These results show that VR technology can improve sustainable health and safety measures in the 4.0 industrial sector. Practical implications include encouraging a sustainable, safety-first attitude among coworkers, enhancing the efficacy of workplace sustainable health and safety training, and improving employees’ self-confidence.